Strategi Pembinaan Disiplin Peserta Didik melalui Pendekatan Konstruktivistik dalam Perspektif Al-Qur'an Surah Luqman Ayat 17 - Imam Syafi'i; Yahya Aziz; Rindu Bunga Kasih Firdauzy; Rosyidah Wardani; Zahwa Machrun Nisa (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
In this era of rapid technological development, promoting student discipline is a major challenge for educators. This research focuses on examining the strategy of promoting student discipline through a constructivist approach from the perspective of QS. This research uses a literature review method with a qualitative descriptive approach. The research data will be taken from the Qur'anic Hadith, various books of Tafsir, articles and relevant journals. The data collected is then analysed in depth in order to draw conclusions. The results show that the constructivist approach is an effective method used to promote student discipline. The strategies used by teachers are role modelling, advice, reward and punishment systems, habituation and special attention to students. In the Islamic perspective, it is also derived from QS. Luqman verse 17 provides a glimpse of disciplining students through the command to pray, amar ma'ruf nahi mungkar, and always be patient in the face of trials. Thus, the application of the constructivist approach in promoting student discipline from the perspective of QS. Luqman verse 17 is very relevant and effective. Thus, this research has been conducted to add insight to the literature for educators, educational institutions and other educational institutions.